Frequency of complementary and alternative medicine usage among Malaysian hypertensive subjects - Ching, Siew Mooi; Vasudevan, Ramachandran; Zakaria, Zainul Amiruddin; Paimin, Fuziah (Marsland Press, 2013)
Hypertension (HPT) is a significant public health problem worldwide. The use of complementary and alternative medicine (CAM) is high among Malaysians particularly with hypertension and diabetes. The objective of this study was to assess prevalence and patterns of CAM used in Klinik kesihatan Salak, a suburban outpatient clinic in Selangor in Malaysia. Face-to-face interview was conducted using a pre-tested structured questionnaire included socio-demographic status, CAM usage, the type, duration and frequency of use, reason and recommendation of CAM, and the expenditure. Of the 300 patient’s approached, 294 patients were selected in the study. Overall CAM usage was 62.6% (184) and the most common CAM products ever used were consuming bitter gourd (34.4%), followed by garlic (17.0%) and Misai Kucing (14.6%).Multiple logistic regression analysis shows that being Muslim, non blue collar and having higher diastolic blood pressure were found to be significantly associated with CAM use. In conclusion, the usage of CAM was high among hypertensive patients in Klinik kesihatan Salak.